The use of problem-based learning in the construction of knowledge in accounting - Urrutia-Heinz, Michele; Costa-Quintana, Alexandre; Capuano-da Cruz, Ana Paula (Revista Electrónica Educare, 2020)
Knowledge, in the Piagetian view, is seen as an element fruit of the interaction of the subject with the environment, understanding the subject as a fundamental being that participates in the process of constructing his knowledge actively. In a similar way, problem-based learning is a teaching technique, which imposes on the student responsibility for his / her knowledge. In this sense, this study sought to verify if the use of an active methodology, specifically problem-based learning, can help in the assimilation of knowledge. For that, a qualitative research was carried out, through a case study, with students of the 4th semester of Accounting Sciences, enrolled in the Structure of the Accounting Statements, in a Federal Higher Education Institution. The application of problem-based learning occurred with the content of the Value Added Statement (DVA). The results show that in general, the use of problem-based learning for content assimilation is significant, since in the first evaluation, after the lecture, the student had more than 58,62% of the students assimilated the content , and after the application of the technique this assimilation passed to 95.23%, revealing that the use of this technique is impressive for the construction of knowledge, besides providing benefits such as the exchange of experience, simulation of a real situation and to develop the ability as the search for solutions.